Conocimientos sobre enfermedades de transmisión sexual en los estudiantes de Bachillerato del Colegio Atahualpa cantón-Machala. - Minga Medina, Mayra Beatriz (2017)
The STD including the HIV/AIDS are a public health issue at national and global level, it affects men and women, especially among teenagers and young people, being the latter vulnerable to get infections due to their sexual behavior and their age. In this context, this investigation has been carried out related with Awareness about Sexual Transmission Diseases at Bachilletato Students at Colegio Atahualpa in Machala Town. Descriptive and transversal study, because of the knowledge determined about sexual transmission diseases in the students, in fact a survey was applied as a technique to collect data, the information was obtained from 291 students who participated freely and voluntarily. This research proposed as a General Objective, to determine the level of awareness of Colegio Atahualpa students in Machala Town about the Sexual Transmission Diseases, on that subject it was proved that the students have awareness about the STD types, identify the signs and symptoms 100%; it is not the same about the awareness about the transmission ways, only the half of them know that they are passed through sexual contact which is worrisome for this vulnerable group of population. Regarding the prevention measures that students could identify it was shown that only half of them mention the use of condoms to protect themselves against STD, a small percentage stated having sex with one partner. Key words: Sexual Transmission Diseases; Students